Function of MYST3 / MOZ: a histone acetyltransferase and chromatin regulator implicated in haematopoietic stem cell development and leukaemia - Monteiro, C.J. (2018)
MOZ (also known as KAT6A and MYST3) is a histone acetyltransferase that is implicated in the development of hematopoietic, heart and craniofacial tissues. Reciprocal translocations generating MOZ fusion proteins are associated with acute myeloid leukaemia (AML), a heterogeneous hematopoietic stem cell disorder where the myeloid cells do not enter into differentiation process, resulting in accumulation of blast cells and absence of a fully functional granulocyte lineage. Also, mutations that truncate the C-terminus of MOZ are associated with global developmental delay. Mechanistically, it is known that MOZ acts as a cofactor for certain transcription factors, particularly those with haematopoietic or neuronal specificity, such as acute myeloid leukaemia/Runt-related transcription factor 1 (AML1/RUNX1) and PU.1. However, at the outset of this project, it was relatively unknown which genes that are regulated by MOZ in leukaemia. Thus, this work investigates MOZ target genes in a leukemic cell line to fully understand its importance in cell function and disease conditions. Firstly, we performed siRNA silencing in K562 cell line, coupled with transcription profiling by RNA sequencing. We identified 406 deregulated genes under MOZ knockdown, of which 76 were downregulated. Many of the MOZ-target genes identified are implicated in haematopoietic development and cell proliferation. Secondly, we generated MOZ/KAT6A knockout K562 cells using CRISPR CAS9n nickase technology. It allowed further analysis of the function of MOZ in leukaemia. Our results confirmed the role of MOZ in maintaining levels of H3K14ac and H3K9ac and an apparent inverse relationship with the levels of H3K14 crotonylation. Furthermore, the results indicated that MOZ is important for leukemic cell proliferation and the gene dosage influences on the cell proliferation rate. Finally, we found that genes requiring MOZ for their expression are sensitive to a novel class of bromodomain inhibitors called iBETs. Furthermore, we found evidence for the existence of MOZ in complex with BRD4 protein. This provides a hitherto unknown link between MOZ, MLL and BRD2-4 complexes and insight into how these epigenetic regulators cooperate to control gene expression.